Multifunctional carbon-doped concrete supercapacitor and preparation method thereof
By leveraging the synergistic effects of functional additives and nano-carbon black, a multifunctional carbon-doped concrete supercapacitor was fabricated, solving the problems of insufficient energy storage performance and limited functionality in existing technologies. This resulted in high energy storage density, good cycle stability and mechanical strength, and stress sensing capabilities.
Patent Information
- Application Number
- CN202610008885.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-06
- Publication Date
- 2026-03-20
AI Technical Summary
Existing cement-based capacitors suffer from low volumetric energy density, insufficient energy storage performance, limited power characteristics, high resistance to electrolyte ion migration, lack of long-term durability and intelligent functions, and fail to be perfectly integrated with concrete structures, thus failing to achieve synergistic optimization of energy storage and mechanical performance.
A multifunctional carbon-doped concrete supercapacitor with high energy density, excellent cycle life, and superior mechanical properties was prepared by using functional additives, high specific surface area nano-carbon black, composite mineral admixtures, and organic electrolyte, and integrated with built-in stress sensing function.
It achieves high energy storage density, good cycle stability, excellent mechanical strength and internal stress sensing capability, solves the performance bottleneck and single function problem in the existing technology, and realizes the integrated design of structure and function.
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of building materials combined with electrochemical energy storage devices, and particularly relates to a multifunctional carbon-doped concrete supercapacitor and a preparation method thereof. BACKGROUND
[0002] As the building material with the largest use and the widest application in the world, concrete has long been mainly used for mechanical support and structure forming. With the acceleration of the transformation of global energy structure to renewable energy, the intermittency and instability of clean power such as solar energy and wind energy have become increasingly prominent. As a huge space carrier, buildings and infrastructure have become a key issue in realizing the goal of low-carbon and sustainable development, that is, how to change them from pure energy consumers to integrated units with energy storage functions.
[0003] The existing solutions mainly install independent energy storage systems such as lithium-ion batteries on the outside of buildings. However, such systems rely on scarce metal resources such as lithium and cobalt, which not only have high costs but also have environmental risks during the life cycle. More importantly, such energy storage systems are physically separated from the main concrete structure and do not fully utilize the volume and mass advantages of building materials. Therefore, it is of great practical significance and broad application prospects to develop an integrated material that can perfectly integrate with the concrete structure, maintain excellent mechanical properties, and have effective electrical energy storage capacity.
[0004] The basic principle is to use the porous structure formed after cement hydration as an ion transmission channel, and at the same time, to construct an electronic conduction network by means of the conductive phase such as carbon black and carbon fiber, so as to form an energy storage body based on the principle of double-layer capacitance. Using such materials to make wall, beam column or pavement components can not only bear the load but also store and release electrical energy.
[0005] However, the existing technical solutions still have the following core problems: first, the volume energy density of the existing cement-based capacitors is low, and the energy storage performance is insufficient, which is difficult to meet the energy storage capacity demand in actual application; second, the power characteristics are limited, the dense concrete matrix leads to large ion pore migration resistance of electrolyte, slow charge and discharge rate, and high internal resistance; third, the long-term durability needs to be broken through, the chemical compatibility of electrolyte and cement hydration products, the stability under dry-wet and freeze-thaw cycles, and the performance degradation in long-term use have not been properly solved; fourth, the function is single, neither the synergistic optimization of the key engineering properties such as the compressive strength, impermeability and freeze-thaw resistance of concrete, nor the exploration of intelligent functions such as stress sensing of the material. SUMMARY
[0006] In order to overcome the defects in the prior art, the application provides a multifunctional carbon-doped concrete supercapacitor and a preparation method thereof.
[0007] In order to achieve the above-mentioned purpose, the application provides the following technical scheme: A multifunctional carbon-doped concrete supercapacitor, raw materials of which include, in mass parts, ordinary portland cement 100 parts, conductive carbon material 15-30 parts, mineral admixture 15-35 parts, water 40-70 parts, polycarboxylate high-performance water reducing agent 0.8-2.0 parts, and functional additives 0.5-5.0 parts; the supercapacitor further comprises an electrolyte impregnated therein.
[0008] The supercapacitor further comprises functional additives, which include, in mass parts, butanediol 1 part, tremella fruiting body extract 0.15-0.35 parts, triterpenoid saponin 0.15-0.35 parts, gum arabic 0.15-0.35 parts, sodium citrate 0.15-0.35 parts, and 1,2-hexanediol 0.15-0.25 parts.
[0009] The functional additives further include vitamin C sodium 0.5-2 parts and carboxymethyl chitosan 0.1-1 parts, and the degree of substitution of the carboxymethyl chitosan ranges from 0.6 to 0.9.
[0010] The preparation method of the tremella fruiting body extract comprises the following steps: The dried tremella fruiting body is crushed and sieved, deionized water is added at a solid-liquid ratio of 1:15 to 1:30, heated and refluxed at 75-90°C for 1.5-3h, filtered, and concentrated to a paste at 60-75°C under reduced pressure to obtain the tremella fruiting body extract.
[0011] The conductive carbon material is nano carbon black, and the specific surface area thereof is 800-1800 square meters per gram.
[0012] The mineral admixture is a mixture of fly ash and granulated blast furnace slag, and the mass ratio of the fly ash to the granulated blast furnace slag is 1:0.5-2.
[0013] The electrolyte is an organic solution of bis (oxalyl) dimethylammonium chloride, and the concentration thereof is 0.8mol / L-1.5mol / L.
[0014] A preparation method of a multifunctional carbon-doped concrete supercapacitor, comprising the following steps: S1. Dry material mixing: the ordinary portland cement, the conductive carbon material, and the mineral admixture are weighed in mass parts and mixed in a dry state for 10 to 25 minutes to obtain a dry mixture; S2. Slurry preparation: Dissolve the functional additives in water, then add the dry mixture and stir for 5-20 min to obtain a flowable slurry; S3. Molding and initial curing: Pour the slurry into a mold and compact it, cover the surface with plastic wrap, and let it stand and cure at a temperature of 20±2℃ and a relative humidity of not less than 95% for 24-48h before demolding; S4. Standard curing and electrode molding: Continue to cure the demolded test piece in a standard curing chamber until the age reaches 25 to 32 days, and cut it into a sheet-shaped electrode block; S5. Capacitor assembly and activation: Stack at least two electrode blocks in parallel with a porous separator in between to form a sandwich structure; immerse the sandwich structure in an electrolyte and soak it at 15-35℃ for 18-36h to allow the electrolyte to fully infiltrate the internal pores of the electrode block.
[0015] In step S2, the components of the functional additives are preheated and stirred in a water bath at 45-60℃ to obtain an additive pre-liquid.
[0016] In step S4, the thickness of the sheet-shaped electrode block is 0.8mm-3.0mm.
[0017] The above technical scheme of the present application has at least the following beneficial effects: 1. The present application introduces a functional additive composed of butanediol, tremella fruiting body extract, triterpenoid saponin, gum arabic, sodium citrate and 1,2-hexanediol, etc., to improve the preparation of the composite material: butanediol and 1,2-hexanediol as co-solvents can promote the dissolution and mutual solubility of each component; tremella fruiting body extract and gum arabic as natural polymer materials can improve the cohesiveness and water retention of the slurry, effectively inhibiting the phenomena of bleeding and delamination; triterpenoid saponin has surface activity, which can reduce the interfacial tension between the liquid and solid phases; sodium citrate can regulate the ionic environment and pH of the system. This functional additive helps to promote the uniform and stable dispersion of conductive carbon materials in the cement slurry, reduces the conductive dead zone formed by agglomeration, and thus forms a continuous and efficient electron conduction network. At the same time, this uniform dispersion state also helps to form a more homogeneous microstructure during subsequent hydration reaction.
[0018] 2. The present application improves the energy density, power characteristics and stability of the charge-discharge cycle capacity of the supercapacitor through the synergistic effect of mineral admixtures and quaternary ammonium salt organic solution; the fine particles of the mineral admixtures can optimize the pore size distribution of the cement stone, increase the number of beneficial micropores, and cooperate with the functional additives to form microstructure channels that are more conducive to ion migration; when the quaternary ammonium salt organic solution is used as the electrolyte, the above-mentioned optimized porous structure helps to fully infiltrate and store the electrolyte, reducing the resistance of ion migration in the pores.
[0019] 3. The present application improves the interface transition zone structure of the cement paste and the conductive carbon network by the physical and chemical synergy between the functional additives and the mineral admixtures, enhances the interface bonding performance between the two phases, so as to guarantee the compressive strength and volume stability meeting the requirements of engineering application while giving the material good electrical conductivity.
[0020] 4. The nano-carbon black conductive network in the present application is sensitive to the mechanical stress and strain of the cement matrix. When the component is subjected to external load, the micro-cracks or deformation of the matrix will change the contact resistance between the nano-carbon black particles, causing regular changes in the resistance of the device. This change can be detected and converted into an electrical signal, so that the supercapacitor of the present application not only has the energy storage function, but also has the ability to convert its mechanical state change into a monitorable electrical signal, realizing the preliminary integration of energy storage and self-monitoring functions. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0022] In the specific implementation of the present application, the sources of various main raw materials are briefly described as follows: Ordinary Portland cement: Hailuo Cement Co., Ltd., P.O42.5 or P.O52.5 grade cement of GB 175-2007.
[0023] Nano-carbon black: Jiangsu Xianfeng Nanometer Material Technology Co., Ltd., Japan Lion ECP-600JD model nano-carbon black, iodine adsorption value 1360 mg / g.
[0024] Butanediol: Shandong Haikexinyuan Material Technology Co., Ltd., 1,4-butanediol (industrial grade, purity ≥ 99%, detection standard according to GB / T24768-2009).
[0025] Tremella fruiting body extract: Xi'an Qiancao Biotechnology Co., Ltd., specifications: 10:1, 20:1 concentration ratio; packaging: 25 kg / barrel or aluminum foil bag.
[0026] Triterpenoid saponin: Wuhan Extract Garden Biotechnology Co., Ltd., purity: ≥98%.
[0027] Arabic gum: Hubei Widel Chemical Technology Co., Ltd., industrial grade product, purity not less than 98%.
[0028] Sodium citrate: Shandong Yingxuan Industrial Co., Ltd., white crystalline powder with a purity of not less than 99%.
[0029] 1,2-Hexanediol: Zhangjiagang Xikai Chemical Co., Ltd., 99% purity, colorless liquid.
[0030] Sodium Vitamin C: Shandong Dibec Bioengineering Co., Ltd., content ≥99.0%.
[0031] Carboxymethyl chitosan: Jiangxi Ruiwei Biotechnology Co., Ltd., degree of substitution > 80%.
[0032] Fly ash: Anhui Conch Cement Group Co., Ltd., Grade II fly ash, loss on ignition ≤8%, fineness (45μm square hole sieve residue) ≤30.0%, water requirement ratio ≤105%, activity index (28d) ≥70%.
[0033] Granulated blast furnace slag: China Salt Inner Mongolia Building Materials Co., Ltd., S95 grade.
[0034] Polycarboxylate high-performance water-reducing agent: Wuhan Subo New Building Materials Co., Ltd., water reduction rate ≥14%, colorless to light yellow liquid in appearance.
[0035] Dioctyl dimethyl ammonium chloride: Wuhan Jushun Chemical Co., Ltd., CAS 5538-94-3, purity 99%.
[0036] The present invention will be described in detail below through examples and comparative examples, but the scope of protection of the present invention is not limited to these examples. Unless otherwise specified, the chemical reagents and raw materials used in the following examples and comparative examples are all conventional commercially available products.
[0037] Example 1 A multifunctional carbon-doped concrete supercapacitor, the raw materials of which, by mass parts, include: 100 parts of ordinary silicate cement, 30 parts of nano carbon black, 35 parts of a mixture of fly ash and granulated blast furnace slag, wherein the mass ratio of fly ash to granulated blast furnace slag is 1:2, 70 parts of water, 2.0 parts of polycarboxylate high-performance water-reducing agent, and 5.0 parts of functional additives.
[0038] The specific composition of the functional additive, by weight, is as follows: 1 part butylene glycol, 0.35 parts Tremella fuciformis extract, 0.15 parts triterpenoid saponins, 0.35 parts gum arabic, 0.15 parts sodium citrate, 0.25 parts 1,2-hexanediol, 2 parts sodium vitamin C, and 1 part carboxymethyl chitosan, with the selected carboxymethyl chitosan having a degree of substitution of 0.9.
[0039] The electrolyte is a 1.5 mol / L dioctyl dimethyl ammonium chloride organic solution.
[0040] The preparation method of the above-mentioned multifunctional carbon-doped concrete supercapacitor is as follows: S1. Dry material mixing: First, prepare the extract of Tremella fuciformis fruiting body for later use. Then, weigh the ordinary silicate cement, nano carbon black, fly ash and granulated blast furnace slag and mix them in a dry state for 25 minutes to obtain dry mixture.
[0041] Specifically, the preparation method of the Tremella fruiting body extract in the above steps is as follows: the dried Tremella fruiting body is crushed and sieved, deionized water is added at a material-to-liquid ratio of 1:30, heated and refluxed at 90°C for 3 hours, filtered, and concentrated under reduced pressure at 75°C to a paste to obtain the Tremella fruiting body extract.
[0042] S2. Slurry preparation: The components of the functional additive are preheated and stirred in a 60°C water bath to form an additive premix. The additive premix is dissolved in water, and then polycarboxylate high-performance water-reducing agent and dry mix are added. The mixture is stirred at an appropriate speed for 20 minutes to obtain a homogeneous slurry with good flowability.
[0043] S3. Molding and initial curing: Pour the slurry into the mold, vibrate it to compact it, cover the surface with plastic wrap, and place it in an environment with a temperature of 22℃ and a relative humidity of not less than 95% for 48 hours to cure. After that, demold to obtain the initial specimen.
[0044] S4. Standard curing and electrode forming: After demolding, the specimen is transferred to the standard curing room for continued curing until the total curing age reaches 32 days. Then, the hardened specimen is cut into sheet electrode blocks with a thickness of 3.0 mm.
[0045] S5. Capacitor assembly and activation: Take two electrode blocks, align them in parallel, and separate them with a porous membrane in the middle to form a sandwich structure; immerse this structure as a whole in the above electrolyte and soak it at 35°C for 36 hours to allow the electrolyte to fully wet the internal pores of the electrode blocks, thus obtaining the supercapacitor.
[0046] Example 2 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: A multifunctional carbon-doped concrete supercapacitor is prepared using a method essentially the same as in Example 1, differing only in the raw material ratio and some process parameters. Specifically, the components, by mass parts, are: 100 parts ordinary silicate cement, 15 parts nano-carbon black, 15 parts a mixture of fly ash and granulated blast furnace slag (with a mass ratio of fly ash to granulated blast furnace slag of 1:0.5), 40 parts water, 0.8 parts polycarboxylate high-performance water-reducing agent, and 0.5 parts functional additives. The functional additives, by mass parts, are: 1 part butanediol, 0.15 parts Tremella fuciformis fruiting body extract, 0.35 parts triterpenoid saponins, 0.15 parts gum arabic, 0.35 parts sodium citrate, 0.15 parts 1,2-hexanediol, 0.5 parts sodium vitamin C, and 0.1 parts carboxymethyl chitosan, with a degree of substitution of 0.6 for the selected carboxymethyl chitosan.
[0047] The electrolyte is a 0.8 mol / L dioctyl dimethyl ammonium chloride organic solution.
[0048] Regarding the preparation process parameters, the dry material mixing time is 10 minutes.
[0049] After the dried Tremella fruiting bodies are pulverized and sieved, deionized water is added at a material-to-liquid ratio of 1:15. The mixture is heated under reflux at 75°C for 1.5 hours, filtered, and then concentrated under reduced pressure at 60°C to a paste to obtain Tremella fruiting body extract.
[0050] During slurry preparation, the preheating temperature was 45℃ and the stirring time was 5 minutes. After the initial curing for 24 hours, standard curing was carried out until the total age reached 25 days. Then, the hardened specimen was cut into sheet electrode blocks with a thickness of 0.8 mm. During the capacitor assembly and activation stage, the immersion temperature was 15℃ and the immersion time was 18 hours. The remaining steps and parameters were completely consistent with those in Example 1.
[0051] Example 3 In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows: A multifunctional carbon-doped concrete supercapacitor is prepared using a method essentially the same as in Example 1, differing only in the raw material ratio and some process parameters. Specifically, the components, by mass parts, are: 100 parts ordinary silicate cement, 22.5 parts nano-carbon black, 25 parts a mixture of fly ash and granulated blast furnace slag (with a fly ash to granulated blast furnace slag mass ratio of 1:1.25), 55 parts water, 1.4 parts polycarboxylate high-performance water-reducing agent, and 2.75 parts functional additives. The functional additives, by mass parts, are: 1 part butanediol, 0.25 parts Tremella fuciformis fruiting body extract, 0.15 parts triterpenoid saponins, 0.25 parts gum arabic, 0.35 parts sodium citrate, 0.20 parts 1,2-hexanediol, 1.25 parts sodium vitamin C, and 0.55 parts carboxymethyl chitosan, with the selected carboxymethyl chitosan having a degree of substitution of 0.75. The electrolyte is a 1.15 mol / L dioctyl dimethyl ammonium chloride organic solution.
[0052] Regarding the preparation process parameters, the dry material mixing time is 17 minutes.
[0053] After the dried Tremella fruiting bodies are pulverized and sieved, deionized water is added at a material-to-liquid ratio of 1:25. The mixture is heated under reflux at 85°C for 2.5 hours, filtered, and then concentrated under reduced pressure at 68°C to a paste-like consistency to obtain the Tremella fruiting body extract.
[0054] During slurry preparation, the preheating temperature was 52℃ and the stirring time was 12 minutes. After the initial curing for 36 hours, standard curing was carried out until the total age reached 28 days. Then, the hardened specimen was cut into sheet electrode blocks with a thickness of 1.9 mm. During the capacitor assembly and activation stage, the immersion temperature was 25℃ and the immersion time was 27 hours. The remaining steps and parameters were completely consistent with those in Example 1.
[0055] Comparative Example 1 In this comparative example, the similarities to Example 1 will not be repeated, and the differences are as follows: It completely excludes the aforementioned functional additives, i.e., it does not contain butylene glycol, Tremella fuciformis fruiting body extract, triterpenoid saponins, gum arabic, sodium citrate, 1,2-hexanediol, sodium vitamin C, and carboxymethyl chitosan. When preparing the slurry, water, polycarboxylic acid high-performance water-reducing agent, and dry mix are directly mixed.
[0056] Comparative Example 2 In this comparative example, the similarities with Example 2 will not be repeated. The differences are as follows: only the extract of Tremella fuciformis fruiting body, gum arabic and carboxymethyl chitosan are removed from the functional additive. The types and amounts of the remaining components in the functional additive are the same as in Example 2.
[0057] Comparative Example 3 In this comparative example, the similarities with Example 3 will not be repeated. The differences are as follows: the conductive carbon material is replaced by an equal mass of ordinary carbon black, which has a specific surface area of about 200 square meters per gram.
[0058] Comparative Example 4 In this comparative example, the similarities with Example 1 will not be repeated. The differences are as follows: only fly ash is used in the mineral admixture, and granulated blast furnace slag is not used. The total amount of fly ash is the same as the total amount of mineral admixture in Example 1.
[0059] Comparative Example 5 In this comparative example, the similarities with Example 1 will not be repeated. The differences are as follows: the electrolyte is not an organic solution of dioctyl dimethyl ammonium chloride, but is replaced with an aqueous solution of potassium chloride of the same concentration.
[0060] Performance Test Results and Analysis To evaluate the performance of the product of this invention, the supercapacitors prepared in the three embodiments and five comparative examples were tested. The test methods are as follows: A Blue Battery testing system was used to conduct charge-discharge tests at a constant current density of 0.5 A / g. The volumetric energy density was calculated based on the discharge curve, and 5000 cycles were performed at a current density of 1 A / g to evaluate the capacity retention rate and characterize the cycle stability. A universal testing machine was used to test the compressive strength of the hardened composite material according to GB / T17671 standard. A precision resistance meter was used in conjunction with a pressure loading device to monitor the change in DC internal resistance of the sample during the slow application of compressive stress. The slope of the linear relationship between the rate of change of internal resistance and stress was calculated as the self-monitoring sensitivity. The test results are summarized in Table 1.
[0061] Table 1 Analysis of Test Results Sample Volume Energy Density (kWh / m3) 5000 Cycle Capacity Retention (%) Compressive Strength (MPa) Self-Monitoring Sensitivity (% / MPa) Example 1 31.2 95.1 26.8 0.12 Example 2 19.5 93.8 24.1 0.09 Example 3 28.7 96.3 27.5 0.14 Comparative Example 1 8.3 67.5 31.2 0.02 Comparative Example 2 15.1 85.2 25.4 0.05 Comparative Example 3 11.4 89.7 26.9 0.04 Comparative Example 4 24.5 91.5 25.0 0.11 Comparative Example 5 16.8 58.3 18.5 0.10 As can be seen from Table 1, all three embodiments exhibit high volumetric energy density, good cycle stability, compressive strength that meets the requirements of structural materials, and clear self-monitoring function.
[0062] Test results show that Example 1 has the highest volumetric energy density due to the use of more conductive carbon materials and functional additives; Example 3 has more balanced values across parameters, exhibiting optimal cycle stability and high overall performance; although some performance indicators of Example 2 are relatively low, they are still far superior to the comparative example, proving that even at the lower limit of parameters, the technical solution of the present invention can still prepare a novel concrete-based energy storage component with high energy density, good cycle life, excellent mechanical strength, and intrinsic stress sensing capability.
[0063] Comparing the experimental data of Example 1 and Comparative Example 1, it can be seen that Comparative Example 1, which did not add functional additives, showed a sharp decrease in both volumetric energy density and cycle retention rate, and its self-monitoring sensitivity was also extremely low. This directly proves that functional additives play a key role in constructing a continuous and efficient conductive network and optimizing the microstructure channels for ion migration. By promoting the dispersion of nano-carbon black and adjusting the properties of the slurry and interface, they have become the core technical basis for achieving high energy storage performance and self-monitoring function in this invention.
[0064] Comparative Example 2 removed the natural polymer components. Although the energy density and self-monitoring sensitivity were improved compared with Comparative Example 1, they were still significantly lower than those of Example 1, and the cycle stability was also reduced. This indicates that the extract of Tremella fuciformis fruiting body, gum arabic and carboxymethyl chitosan have an irreplaceable synergistic effect in improving slurry uniformity and enhancing interfacial adhesion, which is the key to achieving stable electrochemical performance and sensitive stress response.
[0065] Comparative Example 3 showed that replacing nano-carbon black with ordinary carbon black resulted in a significant deterioration of various electrochemical properties, which demonstrates the essential necessity of high specific surface area nano-carbon black for providing sufficient charge adsorption interfaces and constructing low-resistance electronic conduction networks.
[0066] Comparative Example 4, which uses only fly ash, shows a slight decrease in compressive strength and some electrochemical properties, indicating that the introduction of granulated blast furnace slag has a positive effect on optimizing pore structure and improving material density and durability.
[0067] Comparative Example 5, which used an aqueous electrolyte, showed a significant decrease in cycle retention and a substantial reduction in compressive strength. This indicates that, compared to aqueous electrolytes, quaternary ammonium salt organic solutions have fundamental advantages in ensuring long-term chemical compatibility with the cement matrix, preventing damage from hydration products, and maintaining structural strength.
[0068] In summary, this invention utilizes the synergistic effects of functional additives, high specific surface area nano-carbon black, composite mineral admixtures, and organic electrolytes to prepare a multifunctional carbon-doped concrete supercapacitor that combines high energy storage density, good cycle life, excellent mechanical strength, and intrinsic stress sensing capability. This effectively overcomes the performance bottlenecks and functional limitations of existing cement-based energy storage materials, achieving an integrated structural and functional design.
[0069] Specifically, the conductive nano-carbon black network uniformly distributed in the cement matrix has a resistance value that is highly sensitive to the mechanical stress or strain borne by the matrix. When the component is subjected to external loads, the microcracks or deformations generated in the cement matrix will change the contact resistance between the nano-carbon black particles, thereby causing a regular change in the resistance of the entire device. This change can be detected by external circuits and converted into an electrical signal. This enables the supercapacitor of the present invention to realize its energy storage function while also having the ability to convert its own mechanical state changes into monitorable electrical signals. This provides the material's intrinsic support for real-time, in-situ sensing of the structural health status and realizes the initial integration of energy storage and self-monitoring functions.
[0070] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A multifunctional carbon-doped concrete supercapacitor, characterized in that: The raw materials, by weight, include 100 parts of ordinary silicate cement, 15-30 parts of conductive carbon material, 15-35 parts of mineral admixture, 40-70 parts of water, 0.8-2.0 parts of polycarboxylate high-performance water-reducing agent, and 0.5-5.0 parts of functional additives; the supercapacitor also includes an electrolyte impregnated therein.
2. The multifunctional carbon-doped concrete supercapacitor according to claim 1, characterized in that: The supercapacitor also includes functional additives, which, by weight, include 1 part butylene glycol, 0.15-0.35 parts Tremella fuciformis fruiting body extract, 0.15-0.35 parts triterpenoid saponins, 0.15-0.35 parts gum arabic, 0.15-0.35 parts sodium citrate, and 0.15-0.25 parts 1,2-hexanediol.
3. A multifunctional carbon-doped concrete supercapacitor according to claim 2, characterized in that: Functional additives also include 0.5-2 parts of sodium vitamin C and 0.1-1 parts of carboxymethyl chitosan, with the degree of substitution of carboxymethyl chitosan ranging from 0.6 to 0.
9.
4. A multifunctional carbon-doped concrete supercapacitor according to claim 2, characterized in that: The preparation method of Tremella fuciformis fruiting body extract includes the following steps: The dried Tremella fruiting bodies are pulverized and sieved. Deionized water is added at a material-to-liquid ratio of 1:15 to 1:
30. The mixture is heated under reflux at 75-90℃ for 1.5-3 hours. After filtration, the mixture is concentrated under reduced pressure at 60-75℃ to a paste-like consistency to obtain the Tremella fruiting body extract.
5. A multifunctional carbon-doped concrete supercapacitor according to claim 2, characterized in that: The conductive carbon material is nano-carbon black, with a specific surface area of 800-1800 square meters per gram.
6. A multifunctional carbon-doped concrete supercapacitor according to claim 2, characterized in that: The mineral admixture is a mixture of fly ash and granulated blast furnace slag, with a mass ratio of fly ash to granulated blast furnace slag of 1:0.5-2.
7. A multifunctional carbon-doped concrete supercapacitor according to claim 2, characterized in that: The electrolyte is an organic solution of dioctyl dimethyl ammonium chloride with a concentration of 0.8 mol / L to 1.5 mol / L.
8. A method for preparing a multifunctional carbon-doped concrete supercapacitor, based on the multifunctional carbon-doped concrete supercapacitor according to any one of claims 3-7, characterized in that, Includes the following steps: S1. Dry mixing: Weigh out ordinary silicate cement, conductive carbon material and mineral admixtures according to the mass fractions and mix them in a dry state for 10 to 25 minutes to obtain dry mix; S2. Slurry preparation: Dissolve the functional additives in water, then add them to the dry mixture and stir for 5-20 minutes to obtain a fluid slurry; S3. Molding and initial curing: Pour the slurry into the mold and vibrate it to compact it. Cover the surface with plastic wrap and let it stand for curing for 24-48 hours at a temperature of 20±2℃ and a relative humidity of not less than 95% before demolding. S4. Standard curing and electrode forming: After demolding, the specimens are cured in a standard curing room until they reach an age of 25 to 32 days, and then cut into sheet electrode blocks; S5. Capacitor assembly and activation: Stack at least two electrode blocks in parallel alignment, separated by a porous membrane to form a sandwich structure; immerse the entire sandwich structure in the electrolyte and soak at 15-35℃ for 18-36 hours to allow the electrolyte to fully wet the pores inside the electrode blocks.
9. The method for preparing a multifunctional carbon-doped concrete supercapacitor according to claim 8, characterized in that: In step S2, the components of the functional additive are preheated and stirred in a water bath at 45-60°C to obtain the additive premix.
10. The method for preparing a multifunctional carbon-doped concrete supercapacitor according to claim 8, characterized in that: In step S4, the thickness of the sheet electrode block is 0.8mm-3.0mm.